Glutamate Levels and Resting Cerebral Blood Flow in Anterior Cingulate Cortex Are Associated at Rest and Immediately Following Infusion of S-Ketamine in Healthy Volunteers - Bojesen, Kirsten Borup; Andersen, Kasper Aagaard; Rasmussen, Sophie Nordahl; Baandrup, Lone; Madsen, Line Malmer; Glenthøj, Birte Yding; Rostrup, Egill; Broberg, Brian Villumsen (Frontiers in Psychiatry, 2018)
Progressive loss of brain tissue is seen in some patients with schizophrenia and might be caused by increased levels of glutamate and resting cerebral blood flow (rCBF) alterations. Animal studies suggest that normalization of glutamate levels decreases rCBF and prevents structural changes in hippocampus. However, the relationship between glutamate and rCBF in anterior cingulate cortex (ACC) of humans has not been studied in the absence of antipsychotics and illness chronicity. Ketamine is a non-competitive N-Methyl-D-Aspartate receptor antagonist that transiently induces schizophrenia-like symptoms and neurobiological disturbances in healthy volunteers (HV). Here, we used S-ketamine challenge to assess if glutamate levels were associated with rCBF in anterior cingulate cortex (ACC) in 25 male HV. Second, we explored if S-ketamine changed neural activity as reflected by rCBF alterations in thalamus and accumbens that are connected with ACC. Glutamatergic metabolites were measured in ACC with magnetic resonance spectroscopy and whole brain rCBF with pseudo-continuous arterial spin labelling on a 3 Tesla MR scanner before, during, and after infusion of S-ketamine (total dose 0.375 mg/kg). In ACC, glutamate levels were associated with rCBF before (p<0.05) and immediately following S-ketamine infusion (p=0.03), but not during and after. S-ketamine increased rCBF in ACC (p<0.001) but not levels of glutamate (p=0.96). In subcortical regions, S-ketamine altered rCBF in left thalamus (p=0.03). Our results suggest that glutamate levels in ACC are associated with rCBF at rest and in the initial phase of an increase. Furthermore, S-ketamine challenge transiently induces abnormal activation of ACC and left thalamus that both are implicated in the pathophysiology of schizophrenia. Future longitudinal studies should investigate if increased glutamate and rCBF are related to progressive loss of brain tissue in initially first-episode patients.